Teacher Allocation and School Performance in Italy - Alex Bryson; Lorenzo Corsini; Irene Martelli (Institute of Labor Economics (IZA), 2020)
Italy's secondary school system has faced funding constraints for many years which limits availability of new permanent job slots for teachers. When permanent posts do arise they are allocated mostly on seniority while merit only plays a small role. Thus, the age distribution of teachers in schools reflects older teachers' preferences which include the amenity of being close to urban centres. Using schools' distance from main urban centres and population size in the school's vicinity to instrument for non-random exposure of schools to older teachers, we show older teachers are detrimental to pupil attainment in secondary schools. The effect is large: a six-year increase in the average age of teachers (roughly similar to the increase that has occurred in the last 20 years) leads to a one standard deviation reduction in the mean graduation mark. The findings suggest there may be value in altering the way teachers are allocated to secondary schools in Italy.
Keywords: J41; J44; J45; J48; J62; M51; M55; 330; pupil attainment; school performance; teacher allocation; teacher age; permanent contracts